Mapping species-habitat associations in lowland Amazonia: an across-scale perspective with biogeographical implications - Moulatlet, Gabriel Massaine (fi=Turun yliopisto|en=University of Turku|, 2017)
Amazonia is the largest continuous forest in the world, and is a terrestrial ecosystem with one of the highest estimated number of plant species globally. Even with the accumulated knowledge on species distributions in lowland Amazonia, long-standing questions as to species-habitat associations remain unanswered. This is because for most parts of Amazonia the associations between species and environmental conditions are still unknown. In this thesis, I investigated species-habitat associations from multiple perspectives. In the first paper I evaluated evidence of community assembly arising from soil vs. hydrological niche partitioning. I found that when soil cation concentrations were relatively uniform, communities of understorey plant species were strongly associated with local hydrological conditions as determined by topography. In the second paper I found that when soil cation concentrations ranged more widely, floristic patterns were strongly associated with soils. Single-species models showed that species’ realized niches are to a large degree defined by soil nutrients and hydrological conditions. In the third paper, species-habitat associations were quantified across potential zones of species turnover. Turnover zones have been hypothesized to be associated with the main rivers of the Amazon basin, if these represent dispersal barriers that trigger vicariance. I showed that a previously mapped, ca. 1000-km-long geological limit in western Amazonia is a biotic boundary associated with high species turnover. Species composition on the western side of the boundary was very different to that on the eastern side. This barrier runs in a northsouth direction perpendicularly to the Juruá River. No barrier effect across the Juruá River was found. It has been assumed that the current positions of rivers in central Amazonia became established in the Pliocene, promoting speciation on both sides of the rivers by vicariance. In the fourth paper, however, I present evidence that central Amazonian river channels and floodplains have continued to be highly dynamic during the Quaternary. This means that current biogeographical models will need to be revised. Lastly, knowledge of species-habitat associations makes spatial predictions of species distributions possible if appropriate environmental data layers are available. In final paper, I used species associations with soil cation concentrations, as measured from soil samples taken in the field, to test whether digital soil maps allow reconstruction of these associations. The correspondence between field and digital data was low, indicating that the mapping of Amazonian diversity needs better digital environmental data. In sum, the results of this thesis suggest that species-habitat associations in Amazonia are strongly related to habitat heterogeneity at different scales. Floristic patterns therefore need to be investigated from different perspectives, to provide a broad picture of how species are currently distributed. This is crucial in an ecosystem that is highly affected by diversity loss.

Amazonia on maailman laajin yhtenäinen metsäalue, jonka kasvilajisto kuuluu maailman monimuotoisimpiin. Vaikka eri kasvilajien levinneisyydestä Amazoniassa on jo kertynyt melko runsaasti tietoa, kasvilajiston ja elinympäristön välisiin suhteisiin liittyy edelleen paljon ratkaisemattomia kysymyksiä. Tässä väitöstutkimuksessa selvitän kasvilajien suhdetta ympäristöön monesta eri näkökulmasta. Väitöstutkimuksen ensimmäisessä osatyössä tutkin, liittyvätkö erot kasviyhteisön lajikoostumuksessa maaperän ravinnepitoisuuden tai kosteuden vaihteluun. Selvisi, että jos ravinnekationipitoisuus oli kasvupaikkojen välillä samankaltainen, kenttäkerroksen kasviyhteisön koostumus riippui voimakkaasti maaperän kosteusolosuhteista, joihin puolestaan vaikuttivat maaston pinnanmuodot ja korkeuserot. Jos taas kationipitoisuuksissa oli enemmän vaihtelua, kasviyhteisön koostumus riippui enemmänkin maaperästä kuin kosteudesta. Lajikohtaiset mallinnukset osoittivat, että maaperän ravinnepitoisuus ja kosteusolot ovat tärkeimmät kasvilajien ekologisia lokeroita rajaavat tekijät. Toisessa osatyössä mitattiin lajien suhdetta ympäristöön lajiston vaihettumavyöhykkeen molemmin puolin. Vaihettumavyöhykkeiden on arveltu olevan yhteydessä Amazonian altaan pääjokiuomiin, jotka saattaisivat muodostaa lajeille leviämisesteitä, ja siten johtaa lajiutumiseen jokien vastakkaisilla puolilla. Osoitimme, että Amazonian länsiosassa jo aiemmin havaittu 1000 kilometrin pituinen geologinen rajapinta on myös bioottinen rajapinta. Rajapinnan länsipuolella lajisto on hyvin erilaista kuin itäpuolella. Tämä rajapinta ylittää Amazonin suuren sivujoen, Juruán, kohtisuoraan pohjois-eteläsuunnassa. Juruá-joella itsellään ei havaittu olevan minkäänlaista rajapintavaikutusta. On oletettu, että keskisen Amazonian suuret joet vakiintuivat nykyisiin uomiinsa jo plioseenikaudella, minkä jälkeen lajiutumista olisi tapahtunut niillä metsäalueilla, joiden välille joet muodostavat leviämisesteen. Tässä työssä osoitamme kuitenkin, että Amazonian jokiuomat ja tulvatasangot ovat olleet erittäin dynaamisia systeemejä vielä kvartäärikaudellakin. Tämä merkitsee sitä, että Amazonian eliömaantieteen perusteita tulee päivittää. Lajien ympäristövasteiden tunteminen mahdollistaa lajien levinneisyyden mallintamisen, jos sopivaa aineistoa ympäristön vaihtelusta on tarjolla. Viimeisessä osatyössä tutkin, ovatko kasvilajien ympäristövasteet samanlaisia maastonäytteiden ja digitaalisten maaperäkarttojen perusteella määritettynä. Niissä oli samankaltaisuutta vain vähän, mikä viittaa siihen, että Amazonian biodiversiteetin kartoittamiseen tarvitaan nykyistä parempaa digitaalista ympäristöaineistoa. Yhteenveto väitöstutkimuksen tuloksista on, että Amazoniassa kasvilajiston ja elinympäristön väliset suhteet ovat vahvasti kytköksissä ympäristöolosuhteiden vaihteluun useassa eri mittakaavassa. Tarvitaan kasvilajiston tutkimusta monista eri näkökulmista, jotta olisi mahdollista saada kattava käsitys siitä, miten lajit ovat nykyään jakautuneet Amazoniassa. Tämä on ensiarvoisen tärkeää, kun kyse on ekosysteemistä, jonka monimuotoisuus hupenee kaiken aikaa.